Quality of life results from a phase 3 study of brentuximab vedotin consolidation following autologous haematopoietic stem cell transplant for persons with Hodgkin lymphoma. (21st September 2016) - Ramsey, Scott D.; Nademanee, Auayporn; Masszi, Tamas; Holowiecki, Jerzy; Abidi, Muneer; Chen, Andy; Stiff, Patrick; Viviani, Simonetta; Sweetenham, John W.; Radford, John; Zhu, Yanyan; Bonthapally, Vijayveer; et al.
Summary: Brentuximab vedotin (BV) significantly improved progression‐free survival in a phase 3 study in patients with relapsed or refractory Hodgkin lymphoma (RR‐HL) post‐autologous‐haematopoietic stem cell transplant (auto‐HSCT); we report the impact of BV on quality of life (QOL) from this trial. The European Quality of Life five dimensions questionnaire was administered at the beginning of each cycle, end of treatment, and every 3 months during follow‐up; index value scores were calculated using the time trade‐off (TTO) method for UK‐weighted value sets. Questionnaire adherence during the trial was 87·5% ( N  =   329). In an intent‐to‐treat analysis, compared with placebo, TTO scores in the BV arm did not exceed the minimally important difference (MID) of 0·08 except at month 15 (−0·084; 95% confidence interval, −0·143 to −0·025). On‐treatment index scores were similar between arms and did not reach the MID at any time point; mixed‐effect modelling showed that BV treatment effect was not significant ( P  =   0·2127). BV‐associated peripheral neuropathy did not meaningfully impact QOL. Utility scores for patients who progressed declined compared with those who did not; TTO scores between these patients exceeded the MID beginning at month 15. In conclusion, QOL decreased modestly with BV consolidation treatment in patients with RR‐HL at high risk of relapse after auto‐HSCT.